Sistem Otomatisasi Pendetiksi Banjiri Dini - Suherman Suherman (Teknik Informatika, Universitas Pelita Bangsa, 2021)
Rainfall is very high in Indonesia often lead to flooding. Therefore we need a tool or an application to monitor symptoms of the onset of a flood like the Arduino microcontroller. Arduino Uno microcontroller can be connected with a sensor that detects the surrounding conditions, one of which air speed sensors and ultrasonic sensors. This app is designed for early detection of potential flooding at a predetermined point. Data required in this application is a large water velocity, water level and also the position of geographic location measured water velocity. Data altitude and speed of the water is processed with fuzzy algorithms to streamline data delivery. Data speed of the water, the water level, and the position of the location is stored in a database server. The goal is that the data speed of the water, the water level, and geographic position can be read in a web application. To send data to a server, use the HTTP protocol with POST function. Delivery of data preceded by connecting to the server. If the server is available, then the next process is to transfer data using the POST function. The web application will be used by the end user. To get the data speed of the water and the water level, a web application must make requests to the server. When an application sends data to the server, the server will automatically send a response to the client application. The test results showed that the ultrasonic sensors are not able to accurately calculate the height of the water. Keyword : Arduino, Fuzzy, Microcontroller, DetectorFlood, Water Speed Sensor.